Разрешенное волшебство: роман / Ник Перумов - Перумов Ник (Абсолютная магия, 2001)
Экземпляры: аб. (20180413) / Инвентарный номер: 58252 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 27 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445